Access to medicines by patients of the primary health care in the Brazilian Unified Health System - Álvares, Juliana; Guerra Junior, Augusto Afonso; Araújo, Vânia Eloisa de; Almeida, Alessandra Maciel; Dias, Carolina Zampirolli; Ascef, Bruna de Oliveira; Costa, Ediná Alves; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Leite, Silvana Nair; Karnikowski, Margô Gomes de Oliveira; Costa, Karen Sarmento; et al. (Revista de Saúde Pública, 2017)
OBJECTIVE: To evaluate the access to medicines in primary health care of the Brazilian Unified Health System (SUS), from the patients’ perspective. METHODS: This is a cross-sectional study that used data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Services, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines), conducted by interviews with 8,591 patients in cities of the five regions of Brazil. Evaluation of access to medicines used concepts proposed by Penshansky and Thomas (1981), according to the dimensions: availability, accessibility, accommodation, acceptability, and affordability. Each dimension was evaluated by its own indicators. RESULTS: For the “availability” dimension, 59.8% of patients reported having full access to medicines, without significant difference between regions. For “accessibility,” 60% of patients declared that the basic health unit (UBS) was not far from their house, 83% said it was very easy/easy to get to the UBS, and most patients reported that they go walking (64.5%). For “accommodation,” UBS was evaluated as very good/good for the items “comfort” (74.2%) and “cleanliness” (90.9%), and 70.8% of patients reported that they do not wait to receive their medicines, although the average waiting time was 32.9 minutes. For “acceptability,” 93.1% of patients reported to be served with respect and courtesy by the staff of the dispensing units and 90.5% declared that the units’ service was very good/good. For “affordability,” 13% of patients reported not being able to buy something important to cover expenses with health problems, and 41.8% of participants pointed out the expense with medicines. CONCLUSIONS: Results show 70%–90% compliance, which is compatible with developed countries. However, access to medicines remains a challenge, because it is still heavily compromised by the low availability of essential medicines in public health units, showing that it does not occur universally, equally, and decisively to the population